Microbiological Study of Cast Posts before Cementation. (20th February 2017) - Vallejo-Labrada, Maricela; Ojeda-Garces, Juan Carlos
Abstract : This study identifies the most common microorganisms present in type III gold cast posts related to pulpal disease and evaluates the sterilization/disinfection method before cementation in the root canal. Forty-five type III gold cast posts were aseptically collected in sterile sealed plastic bags and taken to the microbiology laboratory to carry out the study: fifteen cast posts had no treatment, fifteen were disinfected (immersion in 70% alcohol during 15 minutes), and fifteen were autoclaved at 121°C for 15 minutes by using saturated steam under 15 psi pressure. By using a two-proportionz -test, the difference was statistically significant (p > 0.05 ) and demonstrates that, in spite of the aseptic pattern used in the cast post collection and laboratory procedures, some cast posts arrive contaminated at the consulting office. The disinfection process worked out in a high percentage and demonstrated that the sterilization by autoclaving eliminated completely the pathogenic microbiota without affecting the cast post shape and integrity that could compromise their final fitting.